ORGANIZATION OF THE INTERNAL AUDIT SERVICE AND ASSESSMENT OF ITS IMPACT ON EFFICIENCY - Shafkarov Fahriddin Khudaiberdievich (American Journals Publishing, 2024)
This article covers the methods of organizing an internal audit, assessing its activities, as well as how an internal audit is carried out in a sanatorium-wellness institution. It is envisaged to achieve the current and strategic objectives of its activities in the sanatorium-wellness institution and to organize an internal audit.In sanatorium-wellness institutions, the risk of organizing an internal audit service and reducing its effectiveness and determining the reasons for their occurrence were identified. It is possible to determine if the institution will increase the effectiveness of the project, ensure savings in funds and achieve efficiency goals. The organization of the Internal audit Service of the sanatorium-wellness institution is discussed. At the first stage for the development of a system of coordinating indicators, the strategic goal of the Internal audit Service is formed and the main factors for achieving it are determined.
Keywords: Financial reporting, accounting, internal financial control, internal audit, Internal audit Service, factor, assessment, efficiency.